Shifting from a thermal-constrained to water-constrained ecosystem over the Tibetan Plateau - Xu, Chaoyi; Liu, Dan; Wang, Xiaoyi; Wang, Tao (Frontiers in Plant Science, 2023)
Understanding the seasonality of vegetation growth is important for maintaining sustainable development of grassland livestock systems over the Tibetan Plateau (TP). Current knowledge of changes in the seasonality of TP grasslands is restricted to spring and autumn phenology, with little known about the date of peak vegetation growth, the most relevant quantity for grassland productivity. Here we investigate the shifts of the date of peak vegetation growth and its climatic controls for the alpine grasslands over the TP during 2001–2020 using a framework based on the law of minimum. The date of peak vegetation growth over the TP advanced by 0.81 days decade-1 during 2001–2020. This spring-ward shift mainly occurs in the semi-humid eastern TP, where the peak growth date tracks the advancing peak precipitation, and shifted towards the timing of peak temperature. The advancing peak growth over the eastern TP significantly stimulated the ecosystem production by 1.99 gCm-2 year-1 day-1 during 2001–2020, while this positive effect weakened from 3.02 gCm-2 year-1 day-1 during 2000s to 1.25 gCm-2 year-1 day-1 during 2010s. Our results highlighted the importance of water availability in vegetation growth over the TP, and indicated that the TP grassland is moving towards a tipping point of transition from thermal-constrained to water-constrained ecosystem under the rapid warming climate.